2004
DOI: 10.1007/s00383-004-1277-5
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric tracheostomy: a 13-year experience

Abstract: Pediatric tracheostomy has been reported to be a surgical procedure with significant morbidity and mortality. The use of tracheostomy in airway management has changed over time as regards indication and outcome. A review of the last 13 years' experience in our institution was carried out to focus on this group of patients and the recent trends in airway management. A retrospective analysis of hospital records was done and information collected with respect to age, gender, indication for tracheostomy, duration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
2
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 14 publications
8
38
2
6
Order By: Relevance
“…Over recent years, numerous studies in different countries have reported the individual experience of various hospitals, with the number of patients varying from 36 to 362 over periods of time ranging from 2 to 37 yrs [3,5,6,8,9,[16][17][18]. Review of these reports reveals differences between the various centres.…”
Section: Discussionmentioning
confidence: 99%
“…Over recent years, numerous studies in different countries have reported the individual experience of various hospitals, with the number of patients varying from 36 to 362 over periods of time ranging from 2 to 37 yrs [3,5,6,8,9,[16][17][18]. Review of these reports reveals differences between the various centres.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] These reviews have reported a mortality rate of 34 -47%, significantly higher than the mortality rates reported in non-cardiac surgical populations. [4][5][6] Two large multi-institutional studies performed by Berry and colleagues 7,8 demonstrated increased risk of in-hospital mortality following tracheostomy in children with congenital heart disease, the majority of whom had undergone cardiac surgical repair or palliation. To our knowledge, no study to date has determined whether tracheostomy following pediatric cardiac surgery continues to be associated with poorer outcomes following hospital discharge relative to patients who require tracheostomy in association with other disease processes.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] The increase in tracheostomies within this age group has been attributed to increases in the survival of premature newborn infants and those requiring prolonged ventilation. 4 The decision to perform a tracheostomy on a child is complex and depends on several factors, including the severity of airway obstruction, the difficulty and duration of intubation and the child's subjacent medical condition. All of these factors must be assessed one by one by the pediatrician and surgeon in conjunction and the indication for tracheostomy must be based on the individual conditions of each child.…”
Section: Indicationsmentioning
confidence: 99%
“…4,15,25,26 The number of complications is even higher during the neonatal period, particularly among preterms, and tracheostomy is considered a high-risk procedure in this age group. 3 This can in part be explained by the smaller tubes used with these children and also by the diseases involved, in particular bronchopulmonary dysplasia.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation